2016
DOI: 10.5505/tjtes.2016.44575
|View full text |Cite
|
Sign up to set email alerts
|

Efficiacy Of Resveratrol And Quercetin After Experimental Spinal Cord İnjury

Abstract: BACKGROUND:The aim of this study was to investigate the effect of natural antioxidants resveratrol and quercetin on oxidative stress and secondary cell damage in rats with acute spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…According to the literature, CoQ10 can modulate apoptosis (Doimo et al, ). Ostrowski and colleagues concluded that use of CoQ10 (10 mg/kg) immediately after trauma had protective effects against ischemic injury in experimental models of ischemia in the brain hemispheres and spinal cord (Erol et al, ; Kerimoğlu et al, ; Ostrowski, , ). In our results we concluded CoQ10 alone could have protective effects on hippocampal injury.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, CoQ10 can modulate apoptosis (Doimo et al, ). Ostrowski and colleagues concluded that use of CoQ10 (10 mg/kg) immediately after trauma had protective effects against ischemic injury in experimental models of ischemia in the brain hemispheres and spinal cord (Erol et al, ; Kerimoğlu et al, ; Ostrowski, , ). In our results we concluded CoQ10 alone could have protective effects on hippocampal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, researchers have reported found that the combination of these two nutraceuticals is useful for preventing tumor angiogenesis and secondary spinal cord injuries. 16,17 However, plant polyphenols are susceptible to chemical degradation during food processing, transport, and storage, especially when exposed to light, heat, and oxygen. They may also be chemically transformed within the human gastrointestinal tract (GIT) due to changes in pH and enzyme activity, which reduces their oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on resveratrol have focused on its effects after SCI (7,13,14,17,20,27,29). These studies have targeted resveratrol's effects on oxidative stress, anti-inflammatory process, and apoptosis.…”
mentioning
confidence: 99%